Fewpal
+2 votes
103 views
in Mathematics by (85 points)

2 Answers

+1 vote
by (25.4k points)
 
Best answer

Solution:

1/(secA - tanA) 
= (secA + tanA)/[(secA + tanA)(secA - tanA)] 
= (secA + tanA)/(sec2A - tan2A) 
= secA + tanA 

because sec2A - tan2A = 1. 

Proof: 
sin2A + cos2A = 1 
sin2A/cos2A + 1 = 1/cos2
tan2A + 1 = sec2
1 = sec2A - tan2A

0 votes
by (1.6k points)

this may be another way 

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...